2015
DOI: 10.15386/cjmed-373
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase Chain Reaction as a Diagnostic Tool for Six Sexually Transmitted Infections - Preliminary Results

Abstract: Background and aimSexually transmitted infections are a very frequent and under-diagnosed cause of illness worldwide. A high number of detection methods and a large range of specimens in which sexually transmitted infections can be determined are available at the moment. Polymerase chain reaction performed on first void urine offers the advantage of being non-invasive, self-collectable and has high sensitivity and specificity. We looked to determine the frequency of Chlamydia trachomatis, Neisseria gonorrhoeae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Considering the debatable role of some of the STI organisms in infection, they may be considered for secondary testing in persistent infections, following negative screening for primary STI pathogens, as is recommended in several countries [ 30 ]. The added value of a multiplex molecular assay for selected STI organisms, especially in a resource limited setting, would significantly improve the current detection rates and result time [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the debatable role of some of the STI organisms in infection, they may be considered for secondary testing in persistent infections, following negative screening for primary STI pathogens, as is recommended in several countries [ 30 ]. The added value of a multiplex molecular assay for selected STI organisms, especially in a resource limited setting, would significantly improve the current detection rates and result time [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained in their study indicated that PCR provides a higher sensitivity and specificity for the detection of the pathogens (culture sensitivity, 71%; PCR sensitivity, 81%; culture specificity, 83%; PCR specificity, 90%) (van der Zee et al, 2016). Similarly, Grad et al (2015), in their study regarding the most common STIs (Chlamydia trachomatis, Neisseria gonorrhoeae, Trichomonas vaginalis, Mycoplasma hominis, Mycoplasma genitalium and Ureaplasma urealyticum) discovered that PCR conveys a higher sensitivity and specificity for symptomatic and asymptomatic patients compared to previous diagnostic tests. It should be noted that PCR represents a more rapid diagnostic test for urine samples and provides the advantages of self-collection and being non-invasive (Grad et al, 2015).…”
Section: Sample Typementioning
confidence: 98%
“…(2015), in their study regarding the most common STIs ( Chlamydia trachomatis , Neisseria gonorrhoeae , Trichomonas vaginalis , Mycoplasma hominis , Mycoplasma genitalium and Ureaplasma urealyticum ) discovered that PCR conveys a higher sensitivity and specificity for symptomatic and asymptomatic patients compared to previous diagnostic tests. It should be noted that PCR represents a more rapid diagnostic test for urine samples and provides the advantages of self‐collection and being non‐invasive (Grad et al., 2015). Methods known to be developed for PCR applications have a high likelihood of working for other amplification methods but may need to be tested to ensure compatibility.…”
Section: Key Considerationsmentioning
confidence: 99%
“…Instead, serological tests that show indirect evidence of infection are commonly used for diagnosis. Polymerase chain reaction (PCR), the laboratory technique of first amplifying DNA segments to better detect them, is of increasing interest in the diagnosis of various sexually transmitted infections (STIs), including gonorrhea (GC), chlamydia (CT), and HIV [14,15]. However, the US Food and Drug Administration (FDA) has not yet approved clinical diagnostic PCR assays for syphilis, and therefore they are not yet available to all clinicians or practice settings [16].…”
Section: Syphilis Diagnosis and Treatmentmentioning
confidence: 99%